Oscillations of a diaphragm under the action of pulse forces - Kirilich, V. M.; Myshkis, A. D.; Prokhorenko, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We investigate the problem of the existence of periodic solutions of the problem of oscillations of a diaphragm with friction and pulse feedback in the case where the times of pulse action are determined by a solution of the system.